Differences in the Genital Microbiota in Women Who Naturally Clear Chlamydia trachomatis Infection Compared to Women Who Do Not Clear; A Pilot Study - Mott, Patricia Dehon; Taylor, Christopher M.; Lillis, Rebecca A.; Ardizzone, Caleb M.; Albritton, Hannah L.; Luo, Meng; Calabresi, Kaitlyn G.; Martin, David H.; Myers, Leann; Quayle, Alison J. (Frontiers in Cellular and Infection Microbiology, 2021)
In vitro studies indicate IFNγ is central to Chlamydia trachomatis (Ct) eradication, but its function may be compromised by anaerobes typically associated with bacterial vaginosis (BV), a frequent co-morbidity in women with Ct. Here we investigated the associations between natural clearance of cervical Ct infection, the vaginal microbiome, and the requirements for IFNγ by evaluating the vaginal microbial and cytokine composition of Ct treatment visit samples from women who cleared Ct infection in the interim between their Ct screening and Ct treatment visit. The pilot cohort was young, predominantly African American, and characterized by a high rate of BV that was treated with metronidazole at the Ct screening visit. The rate of natural Ct clearance was 23.6% by the Ct treatment visit (median 9 days). 16S rRNA gene sequencing revealed that metronidazole-treated women who had a Lactobacillus spp.-dominant vaginal microbiota (CST 2 or 3) at the Ct treatment visit, were more prevalent in the Ct clearing population than the non-clearing population (86% v. 50%). L. iners (CST2) was the major Lactobacillus spp. present in Ct clearers, and 33% still remained anaerobe-dominant (CST1). Vaginal IFNγ levels were not significantly different in Ct clearers and non-clearers and were several logs lower than that required for killing Ct in vitro. An expanded panel of IFNγ-induced and proinflammatory cytokines and chemokines also did not reveal differences between Ct clearers and non-clearers, but, rather, suggested signatures better associated with specific CSTs. Taken together, these findings suggest that BV-associated bacteria may impede Ct clearance, but a Lactobacillus spp.-dominant microbiome is not an absolute requirement to clear. Further, IFNγ may be required at lower concentrations than in vitro modeling indicates, suggesting it may act together with other factors in vivo. Data also revealed that the vaginal bacteria-driven inflammation add complexity to the genital cytokine milieu, but changes in this microbiota may contribute to, or provide cytokine biomarkers, for a shift to Ct clearance.